Correlated proton-electron hole dynamics in protonated water clusters upon extreme ultraviolet photoionization - Zheng Li; Oriol Vendrell (Structural Dynamics, 2016)
The ultrafast nuclear and electronic dynamics of protonated water clusters H+(H2O)n after extreme ultraviolet photoionization is investigated. In particular, we focus on cluster cations with n = 3, 6, and 21. Upon ionization, two positive charges are present in the cluster related to the excess proton and the missing electron, respectively. A correlation is found between the cluster's geometrical conformation and initial electronic energy with the size of the final fragments produced. For situations in which the electron hole and proton are initially spatially close, the two entities become correlated and separate in a time-scale of 20 to 40 fs driven by strong non-adiabatic effects.